South African Indian pamphlets : a collection of publications of South African Indian organizations and Indian government publications regarding Indians in South Africa (Yale University Library, 1982)
Consists of pamphlets published 1914-1915 by various South African Indian organizations and by the Indian government concerning Indians in South Africa.